“From the history of Muslims to Muslims in History: Some critical notes on ‘Arab-Islamic Studies’ in Portugal”, Hamsa. Journal of Judaic and Islamic Studies 1 (2014): 29-40 - Barros, Maria Filomena Lopes de (2014)
The Arabic-Islamic studies in Portugal reveal some particularities within the European context. The comparison with Spain shows the structural differences that, from its origin in the 18th century, reveal a discontinuity investment in the Arabic language, which never evolved into an independent philological framework. Moreover, the history of Muslims, as an integral part of the Portuguese past only begins to re-inscribe in the discourse of social and human sciences after the 1974 Revolution, in a paradigm shift not yet fully achieved.